Prawne możliwości realizacji usług badawczo-rozwojowych w postaci pomocy publicznej w ramach Programu Operacyjnego Innowacyjna Gospodarka - Onufer, Mariusz; Burawski, Dariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The goal of the paper is to present the main characteristics of the “Innovative Economy” Operational Programme, and in particular the possibilities for subsidising companies’ innovative activities. Public aid is strictly regulated by the EU law, but the “Innovative Economy” Operational Programme gives companies specific possibilities for receiving funds for their innovative activities. The “Innovative Economy” Operational Programme is a multi-annual 2007–2013 programme to improve innovative initiatives and support development and implementation of research and development R&D and ICT in Poland. An important part of the EU economic policy is delivering to companies especially small and medium good conditions for improving innovation, with an emphasis on R&D activities. Because of the perceived importance of subsidising them, public money was included in the Programme. The Programme guarantees money from structural funds to support so called ‘centers of innovation”. As a result, these centers are obliged to deliver financial support to companies, with one of the forms of this support being delivered as R&D services. Because receiving such services is a kind of financialbenefit for a company, it must be treated as a public aid. In the case of this specific service, public aid is described as a de minimis support.
Keywords: usługi badawczo-rozwojowe; pomoc publiczna; Program Operacyjny Innowacyjna Gospodarka